2021
DOI: 10.3390/ijms22020542
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular Vesicles: The Missing Link between Physical Exercise and Depression Management?

Abstract: Depression is associated with an increased risk of aging-related diseases. It is also seemingly a common psychological reaction to pandemic outbreaks with forced quarantines and lockdowns. Thus, depression represents, now more than ever, a major global health burden with therapeutic management challenges. Clinical data highlights that physical exercise is gaining momentum as a non-pharmacological intervention in depressive disorders. Although it may contribute to the reduction of systemic inflammation associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 119 publications
0
12
0
Order By: Relevance
“…Endurance exercise has been shown to alter EV profiles ( Oliveira et al, 2020 ; Soares et al, 2021 ). Chronic exercise in murine models (3weeks swim training) was, for example, shown to significantly increase serum EV count ( Bei et al, 2017 ), whilst the modal size of EVs was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Endurance exercise has been shown to alter EV profiles ( Oliveira et al, 2020 ; Soares et al, 2021 ). Chronic exercise in murine models (3weeks swim training) was, for example, shown to significantly increase serum EV count ( Bei et al, 2017 ), whilst the modal size of EVs was unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…the PD cell model [204]. Simultaneously, circ_0070441 can directly bind to miR-626, thereby indirectly regulating IRS2 expression, and its upregulation was verified to aggregate MPP(+)-induced neurotoxicity in a PD cell model [205]. However, there is still a controversial issue about whether circRNAs can serve as miRNA sponges because some studies have revealed that most circRNAs do not have the function of sponging miRNAs [211] (Figure 5).…”
Section: Cerna In the Pathogenesis And Neuroinflammation Of Pdmentioning
confidence: 99%
“…Therefore, the discovery of minimally invasive biomarkers is of great interest. Circulating cell-free miRNAs exist in the extracellular circulation, including plasma, serum, cerebrospinal fluid, saliva, urine, breast milk, and seminal plasma [ 205 ]. They are stable in severe environmental conditions and resistant to cellular RNase in circular systems owing to their existence in extracellular spaces [ 206 , 207 ].…”
Section: Microrna (Mirna)mentioning
confidence: 99%
“…MiRNAs control gene expression by binding to imperfect complementary sites within the 3′ untranslated regions of their mRNA targets and orchestrate their degradation and/or post-transcriptional repression [ 286 , 287 ]. MiRNAs are involved in the control of all normal biological processes and their expression deregulation (i.e., increased or decreased expression) has been associated with the initiation and development of cancers [ 288 , 289 , 290 , 291 ]. Mature and functional cellular miRNAs can be detected in the blood and other biological fluids and can generally be found in two forms: either as cell/membrane-free molecules (i.e., free, bound to Argonaute (Argo) or to nucleophosmin proteins, complexed with high density lipoprotein (HDL)) or encapsulated within extracellular vesicles [ 274 , 291 , 292 ].…”
Section: Exosomes: a Source Of Tumor Biomarkersmentioning
confidence: 99%